Cancer-associated fibroblasts-derived IL-8 mediates resistance to cisplatin in human gastric cancer. (10th July 2019) - Zhai, Jing; Shen, Jiajia; Xie, Guiping; Wu, Jiaqi; He, Mingfang; Gao, Lili; Zhang, Yifen; Yao, Xuequan; Shen, Lizong
Abstract: Chemoresistance remains the major obstacle to achieve optimal prognosis in gastric cancer patients, and the underlying molecular mechanisms of cancer-associated fibroblasts (CAFs) in gastric cancer chemoresistance remain poorly understood. We identified the high pretherapeutical serum IL-8 level in gastric cancer patients was associated with poor response to platinum-based therapy, and it increased gradually during neoadjuvant chemotherapy and it decreased after radical surgery. Immunohistochemistry assays showed that IL-8 was highly expressed in gastric cancer tissues in chemoresistant patients, and located in CAFs. Primary CAFs produced more IL-8 than the corresponding normal fibroblasts, and human stomach fibroblast line Hs738 secreted more IL-8 after co-cultured with conditioned media from AGS or MGC-803 cells. IL-8 increased the IC50 of cisplatin (CDDP) in AGS or MGC-803 in vitro . Simultaneously, IL-8 treatment enhanced the expression of PI3K, phosphorylated-AKT (p-AKT), phosphorylated-IKb (p-IKb), phosphorylated-p65 (p-p65) and ABCB1, and ABCB1 and p-p65 were overexpressed in tumor tissues of chemoresistant patients. Collectively, CAFs derived IL-8 promotes chemoresistance in human gastric cancer via NF-κB activation and ABCB1 up-regulation. Our study provides a novel strategy to improve the chemotherapeutical efficacy and the prognosis of gastric cancer. Graphical abstract: Image 1 Highlights: The high serum IL-8 level was related to poor response to platinum-based therapy. IL-8 was highly expressed in cancer-associated fibroblast in chemoresistant patient. IL-8 increased the IC50 of cisplatin in AGS or MGC-803 in vitro . IL-8 treatment enhanced the expression of p-AKT, p-IKb, p-p65 and ABCB1. ABCB1 and p-p65 were overexpressed in tumor tissues of chemoresistant patients.